LEDLIDI ( coconut leaf stick lighting ) / Asrol Hasan…[et al.] - Hasan, Asrol; Ahmad Sayuti, Nurul `Ayn; Nawi, Azmir Mamat; Ibrahim, Syazliyati; Ab Hamid, Abu Hanifa (Universiti Teknologi MARA, Kedah, 2018)
Craft Industry has been developed as part of the Creative Industry Policy in Malaysia (DIKN) which was launched in 2009. The creative industries have become a focused policy area for the Malaysian government which is in Line with the Vision 2020. The Malaysian craft industry used to focus on weaving products such as basket or other daily use craft products from rattan and bamboo rather than exploring other natural materials. Although other handmade craft products which are created using natural resources (from the coconut tree, banana trunk. eggshells, etc.) are seen to have commercial values, some of these materials are still undervalued and not fully recognised in the craft industries. One of the most undervalued natural material is coconut leaf stick which has not been seriously considered as a core substance in the craft industries in Malaysia. Opnsidei ing this. this study is carried out to explore the potential use of coconut sticks in product design. The LEDLIDI is designed to give new dimensions in the development of creative products in Malaysia which focuses more on lighting design or home interior decoration products that are made from coconut leaf sticks. This project focuses on the development process. ideas generation and material exploration where coconut stick is identified to have aesthetical commercial values. diverse usage and durable features. The LEDLIDI is uniquely designed to be multifunctional and can be converted into a table light. a freestanding light and a pendant light. The silhouette which is projected from the arrangement of the coconut sticks will not only illuminate but create an ambience for modern contemporary living spaces. One of the significant impacts of this project is to give ideas and be an exponent for cottage industries to explore more natural materials for craft production in their designs. It is hoped that the use of coconut leaf sticks can help the craft industries' entrepreneurs to develop and produce more home interior craft products which are able to compete in the global market.